ISSA 5000: key features of the International Sustainability Assurance Standard - Nancy Kamp-Roelands (MAB)
The article describes the structure and key concepts within the International Standard on Sustainability Assurance (ISSA) 5000 ‘General requirements for sustainability assurance engagements’. Because this international standard will form an important basis for the European sustainability assurance standards to be issued in 2026 the article also briefly discusses the relationship with the European developments and the Dutch sustainability assurance standard NV COS 3810N.